Design of a novel optical sensor for determination of trace amounts of copper by UV–visible spectrophotometry in real samples. (24th November 2017) - Pourbasheer, Eslam; Morsali, Somayeh; Azari, Zhila; Karimi, Mohammad Ali; Ganjali, Mohammad Reza
Abstract : A new optical chemical sensor is established for sensitive and selective spectrophotometric detection of copper based on the immobilization of 3‐(2‐methyl‐2, 3‐dihydro‐1, 3‐benzothiezol‐2‐yl)‐2 H ‐chromen‐2‐one on a triacetylcellulose membrane. Copper ions react with the immobilized ligand and cause an increase in the absorption of the membrane at 550 nm in universal buffer solution at pH = 6. The effects of pH, indicator concentration and reaction time on the immobilization of the ligand were studied. This optode exhibits a linear range of 7.0 × 10 −7 to 1 × 10 −4 mol l −1 of copper ion concentration with a limit of detection of 3.0 × 10 −7 mol l −1 . The response time of the newly designed optode is within 3 min. The effect of different possible interfering species was investigated and it was found that the sensor has very good selectivity. The proposed sensor benefits from advantages such as low cost, high stability, low detection limit, fast response time, reproducibility, relatively long lifetime, and good selectivity for Cu 2+ ion determination among a large number of alkali, alkaline earth, transition and heavy metal ions. The sensor can readily be regenerated with thiourea solution and its response is reversible and reproducible (relative standard deviation < 1.4%). The proposed optode was applied successfully for the determination of Cu(II) in various samples. Abstract : The characterization of an optode is described, which was used for determination of copper. The effects of pH, indicator concentration and reaction time on the immobilization of ligand were studied. The optical sensor was successfully applied for the determination of Cu(II) in various samples.